Applying Behavioral Conditioning to Identify Anticipatory Behaviors. Issue 2 (3rd April 2017) - Krebs, Bethany L.; Torres, Erika; Chesney, Charlie; Kantoniemi Moon, Veronica; Watters, Jason V.
ABSTRACT: The ability to predict regular events can be adaptive for nonhuman animals living in an otherwise unpredictable environment. Animals may exhibit behavioral changes preceding a predictable event; such changes reflect anticipatory behavior. Anticipatory behavior is broadly defined as a goal-directed increase in activity preceding a predictable event and can be useful for assessing well being in animals in captivity. Anticipation may look different in different animals, however, necessitating methods to generate and study anticipatory behaviors across species. This article includes a proposed method for generating and describing anticipatory behavior in zoos using behavioral conditioning. The article also includes discussion of case studies of the proposed method with 2 animals at the San Francisco Zoo: a silverback gorilla ( Gorilla gorilla gorilla ) and a red panda ( Ailurus fulgens ). The study evidence supports anticipation in both animals. As behavioral conditioning can be used with many animals, the proposed method provides a practical approach for using anticipatory behavior to assess animal well being in zoos.